การประเมินบุคคล : การใช้ผลการประเมินและบทบาทนักประเมิน: Personnel Evaluation : Using Evaluation and The Role of Evaluator - Buosonte, Rattana (Asian Health, Science and Technology Reports, 2010)
Personnel Evaluation is a systematic process for gathering information of person’s characteristic and performance behavior in order to use those obtained information to determine value and quality of that person. Its main aim is to adaptation and development the performance of that person. In order that the personnel evaluation, The person who perform evaluation or evaluator have to be a person who got an acceptance in the moral of evaluator profession in order to guarantee that the evaluator will be evaluate the others believable in line with Standards of evaluation and Guiding principle for evaluators. In the use of personnel evaluation result must be for improve those person not for catch up, deprive, remove, relieve or discharge the person that known as pseudo evaluation.